Functional Outcome of Arthroscopic Suture Pull-Out Fixation in Tibial Spine Avulsion of Anterior Cruciate Ligament - Hamal, Bhadra; Regmi, Utsav; Bhandari, Dinesh; Thapa, Pralhad; Chaurasia, Roshan Bhagat; Yadav, Sanjay Kumar (Journal of Nepal Health Research Council, 2024)
Background: Tibial spine avulsion of the anterior cruciate ligament is a rare intraarticular injury of the knee. In this condition, the tibial attachment site of the anterior cruciate ligament is detached from the knee. The mechanism of the injury is hyperextension of the knee and rotation with valgus force. There are so many treatment options. This study aims to find out the functional outcome of Arthroscopic Suture pull-out fixation in this injury. Methods: This is a retrospective study done from August 15, 2019, to August 14, 2022. The outcome was analyzed by comparing the preoperative and 12-month postoperative International Knee Documentation Committee Score, Tegner Lysholm Score, Knee Range of motion, and Visual Analog Scale Score. Results: Twenty-two patients were included with a mean age of 18.95 (13-31). Among them 15(68.2%) were male and 7(31.8%) were female. Arthroscopic suture pull-out fixation was done in all the cases. The knee range of motion was improved from preoperatively 35.00±7.86 to 135.68±3.50 at the final follow-up. The Tegner Lysholm score was improved from preoperatively 34.68±1.28 to 94.54±2.97 at the final follow-up. Preoperatively the VAS score was 8.04±1.27 which improved to 0.60±0.50 at the final follow-up. The IKDC score was 23.86±1.42 preoperatively which improved to 92.72±3.28 at the final follow-up with p-value < 0.001 Conclusions: Arthroscopic Suture pull-out fixation of tibial spine avulsion of the Anterior cruciate ligament is a good technique that restores the functions of the knee and has an excellent outcome Keywords: Anterior cruciate ligament; suture pull-out fixation; tibial spine avulsion.